Molecular Epidemiology, Antibiotic Resistance, and Virulence Traits of Stenotrophomonas maltophilia Strains Associated With an Outbreak in a Mexican Tertiary Care Hospital - Cruz-Córdova, Ariadnna; Mancilla-Rojano, Jetsi; Luna-Pineda, Víctor M.; Escalona-Venegas, Gerardo; Cázares-Domínguez, Vicenta; Ormsby, Christopher; Franco-Hernández, Isabel; Zavala-Vega, Sergio; Hernández, Mónica Andrés; Medina-Pelcastre, Marisol; Parra-Ortega, Israel; Rosa-Zamboni, Daniela De la; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Stenotrophomonas maltophilia, an emerging opportunistic pathogen, is widely distributed in the environment, and the resistance mechanisms and virulence factors of this bacterium facilitate its dissemination in hospitals. This study aimed to characterize the molecular epidemiology of S. maltophilia strains associated with an outbreak in the Children’s Hospital of México Federico Gómez (HIMFG). Twenty-one clinical S. maltophilia strains were recovered from cultures of blood and urine samples from 10 pediatric patients at the emergency department, and nine environmental S. maltophilia strains recovered from faucets in the same area were also included. Two of the 10 patients were related with health care-associated infections (HCAIs), and the other eight patients (8/10) were infected with environmental S. maltophilia strains. The outbreak was controlled by monthly disinfection of the faucets in the emergency department. Typing using pulsed-field gel electrophoresis (PFGE) showed a 52% genetic diversity with seven pulsotypes denoted P1 to P7 among all S. maltophilia strains. Three pulsotypes (P2, P3, and P7) were identified among both the clinical and environmental S. maltophilia strains and associated with two type sequences (STs), namely, ST304 and ST24. Moreover, 80% (24/30) of the strains exhibited resistance mainly to tetracycline, 76.66% (23/30) to trimethoprim-sulfamethoxazole, and 23.33% (7/30) to the extended-spectrum β-lactamase (ESBL) phenotype. The resistance genes identified by multiplex PCR were the following: sul1 in 100% (30/30), qnr in 86.66% (26/30), and intl1 in 80% (24/30) of the samples. Furthermore, the pilU, hlylII, and rmlA genes were identified in 96.6% (29/30), 90% (27/30), and 83.33% (25/30) of the samples, respectively. Additionally, 76.66% (23/30) of the S. maltophilia strains exhibited high swimming motility, 46.66% (14/30) showed moderate biofilm formation capacity, 43.33% (13/30) displayed moderate twitching motility, and 20% (6/30) exhibited high adherence. The clinical S. maltophilia strains isolated from blood most strongly adhered to HTB-9 cells. In conclusion, the molecular epidemiology and some of the features such as resistance, and virulence genes associated with colonization patterns are pathogenic attributes that can promote S. maltophilia dissemination, persistence, and facilitate the outbreak that occurred in the HIMFG. This study supports the need for faucet disinfection as a control strategy for clinical outbreaks.